A comparison of medley and freestyle performance for national and international swimmers between 1994 and 2011 - Buhl, C.; Knechtle, B.; Rüst, C. A.; Rosemann, T.; Lepers, R. (Open Access Journal of Sports Medicine, 2013)
The change in swim performance over time has been investigated for freestyle, but not for other strokes, such as in the medley. The aim of the study was to examine changes in 200 m and 400 m swim performances in medley swimmers at national (Switzerland) and international level (world championship finals) from 1994 to 2011. The 200 m and 400 m freestyle performances were also analyzed for comparison. Swim performances were analyzed using linear regression and one-way analysis of variance. Male Swiss swimmers improved swim speed by 5.4% in the 200 m medley, 5.3% in the 200 m freestyle, 5.1% in the 400 m medley, and 5.7% in the 400 m freestyle (P < 0.01). Female Swiss swimmers improved swim speed by 4.4% in the 200 m medley, 3.3% in the 200 m freestyle, 3.9% in the 400 m medley, and 3.4% in the 400 m freestyle (P < 0.05). Male swimmers at international level improved swim speed by 4.5% in the 200 m medley, 4.6% in the 200 m freestyle, 2.6% in the 400 m medley, and 2.7% in the 400 m freestyle (P < 0.01). Female swimmers improved swim speed by 4.3% in the 200 m medley, 3.5% in the 400 m medley, and 3.1% in the 400 m freestyle (P = 0.02), but 200 m freestyle performance remained unchanged (P > 0.05). The sex difference in national swim performance remained unchanged at 10.2% ± 0.6% for the 200 m medley (P > 0.05) and increased from 8.8% to 9.8% for the 400 m medley (P < 0.05). In freestyle, it increased from 8.8% to 10.7% in the 200 m, and from 7.8% to 9.4% in the 400 m (P < 0.01). The sex difference in international athletes remained unchanged at 11.1% ± 0.9% in the 200 m medley, 10.1% ± 0.8% in the 400 m medley, 10.0% ± 1.3% in the 200 m, and 9.2% ± 0.6% in the 400 m freestyle (P > 0.05). For the 400 m medley, the sex difference was lower compared to the 200 m medley for national (9.3% ± 0.8% vs 10.2% ± 0.6%, P = 0.01) and for international (10.1% ± 0.8% vs 11.1% ± 0.9%) athletes. For the 400 m freestyle, the sex difference was lower compared to the 200 m freestyle for national (7.9% ± 0.9% vs 9.3% ± 0.8%) and international (9.2% ± 0.6% vs 10.0% ± 1.3%) athletes (P < 0.01), and lower in the freestyle than the medley for the same distances (P < 0.01). Future studies should investigate the reasons for the greater sex difference in the medley than the freestyle.